2018
DOI: 10.3390/nu10050546
|View full text |Cite
|
Sign up to set email alerts
|

Italian Association of Clinical Endocrinologists (AME) and Italian Chapter of the American Association of Clinical Endocrinologists (AACE) Position Statement: Clinical Management of Vitamin D Deficiency in Adults

Abstract: Vitamin D deficiency is very common and prescriptions of both assay and supplementation are increasing more and more. Health expenditure is exponentially increasing, thus it is timely and appropriate to establish rules. The Italian Association of Clinical Endocrinologists appointed a task force to review literature about vitamin D deficiency in adults. Four topics were identified as worthy for the practicing clinicians. For each topic recommendations based on scientific evidence and clinical practice were issu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
77
1
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(83 citation statements)
references
References 139 publications
0
77
1
4
Order By: Relevance
“…In order to understand these conflicting results, it is important to highlight that the subjects included in those papers were not affected by hypovitaminosis D and were treated with doses much higher than the ones recommended in clinic [19]. Hence, the conclusions from those papers can only be that too much vitamin D, if it is not needed, may be detrimental for unknown reasons.…”
Section: Vitamin D Supplements and Muscle Healthmentioning
confidence: 99%
“…In order to understand these conflicting results, it is important to highlight that the subjects included in those papers were not affected by hypovitaminosis D and were treated with doses much higher than the ones recommended in clinic [19]. Hence, the conclusions from those papers can only be that too much vitamin D, if it is not needed, may be detrimental for unknown reasons.…”
Section: Vitamin D Supplements and Muscle Healthmentioning
confidence: 99%
“…The EFSA Panel stated that it should be clearly specified if certain subgroups of the population are excluded from the intended uses (e.g., pregnant and lactating women, infants) [6]. Rizzo et al [8] concluded that evidence from clinical trials is inadequate to draft any definitive conclusion regarding vitamin D supplementation in pregnant women and there are still unanswered questions regarding vitamin D supplementation and target levels also for the general population [9,10].…”
mentioning
confidence: 99%
“…However, the interpretation of 25(OH)D and 24,25(OH) 2 D results is still a matter of intensive debate. Previous studies have established reference intervals [17,18] and clinical cut-offs [19][20][21][22]. However, the close relationship between 25(OH)D and 24,25(OH) 2 D implies that a meaningful interpretation is only possible when both metabolites are considered together.…”
mentioning
confidence: 99%
“…Cavalier et al suggest that in clinical practice the concentrations of 24,25(OH) 2 D and 25(OH)D should be reported together with the probability that this constellation occurs in healthy subjects. This information would help physicians judging their patients' metabolic status in a more dynamic fashion and leave the historical concept of vitamin D deficiency on the basis of a universal 25(OH)D cut-off [19][20][21][22]. With the established 25(OH)D cut-offs a large portion of the population has vitamin D deficiency or at least insufficiency,…”
mentioning
confidence: 99%
See 1 more Smart Citation